2006
DOI: 10.1002/mus.20568
|View full text |Cite
|
Sign up to set email alerts
|

Concentric‐needle single‐fiber electromyography for the diagnosis of myasthenia gravis

Abstract: The goal of this study was to estimate the accuracy of concentric-needle single-fiber electromyography (CN-SFEMG) for the diagnosis of myasthenia gravis (MG). A consecutive series of patients referred for CN-SFEMG was evaluated by an investigator blinded to the results of CN-SFEMG in order to determine the presence or absence of MG using an independent reference standard. Sensitivity, specificity, predictive values, and likelihood ratios were calculated. The study population included 51 patients (21 with MG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 23 publications
(34 reference statements)
4
72
1
4
Order By: Relevance
“…24 In ocular MG, SFEMG is considered the diagnostic gold standard, as reflected by four studies reporting a high sensitivity of 92-97% [25][26][27][28] , although two other groups found lower sensitivities of 83% and 62%. 29,30 Comparison of different electromyographic tests in ocular MG demonstrated that the closer the measurement to the extraocular muscles, the higher the sensitivity. In contrast to SFEMG, oVEMP not only directly assess the extraocular muscles, but is also better tolerated, because it is less invasive, less cumbersome and less operator-dependent.…”
Section: Ovemp In Mgmentioning
confidence: 99%
“…24 In ocular MG, SFEMG is considered the diagnostic gold standard, as reflected by four studies reporting a high sensitivity of 92-97% [25][26][27][28] , although two other groups found lower sensitivities of 83% and 62%. 29,30 Comparison of different electromyographic tests in ocular MG demonstrated that the closer the measurement to the extraocular muscles, the higher the sensitivity. In contrast to SFEMG, oVEMP not only directly assess the extraocular muscles, but is also better tolerated, because it is less invasive, less cumbersome and less operator-dependent.…”
Section: Ovemp In Mgmentioning
confidence: 99%
“…The recording allows a high recording selectivity, which is further increased by filtering the low-frequency components (high pass filter) to reduce the contribution from distant muscle fibers which contains relatively more low frequency components than high frequency components compared to signals adjacent to the recording tip 2 . The use of a reusable electrode as the specific SFEMG has raised concern regarding the risk of transmission of infectious agents such as prion disease 10,11 . Because of that, attempts are being in course to use disposable concentric needle electrode (CNE) 8,10,11 .…”
mentioning
confidence: 99%
“…The use of a reusable electrode as the specific SFEMG has raised concern regarding the risk of transmission of infectious agents such as prion disease 10,11 . Because of that, attempts are being in course to use disposable concentric needle electrode (CNE) 8,10,11 . The low-frequency filter should then typically be raised from 500 Hz to 1-2 kHz in order to suppress activity from distant muscle fibers 10,11 .…”
mentioning
confidence: 99%
“…Recentemente, com a necessidade crescente de utilização de material descartável em procedimentos médicos, incluindo os eletrodos de agulha utilizados em eletroneuromiografia (ENMG), iniciou-se uma série de estudos usando eletrodos de agulha convencionais descartáveis, por exemplo, a agulha monopolar (Wiechers, 1985;Buchman, Garratt, 1992;Tutkavul, Baslo, 2010) e a agulha concêntrica (AC) (Ertaş et al, 2000;Benatar et al, 2006;Sarrigiannis et al, 2006;Kouyoumdjian, Stålberg, 2007;2008a;2008b;2013a). Em comparação com as agulhas monopolar e concêntrica, a AFU possui área de registro muito mais seletiva (King et al, 1997).…”
Section: Introductionunclassified
“…Adicionalmente à filtragem de sinais, são necessários cuidados técnicos na aceitação dos PAs obtidos com AC para análise do jitter (Sanders, Stålberg, 1996;Ertaş et al, 2000;Benatar et al, 2006;Sarrigiannis et al, 2006;Kouyoumdjian, Stålberg, 2007;Stålberg, Sanders, 2009 (Stålberg, Sanders, 2009;Stålberg et al, 2010). Além da velocidade de propagação nas fibras musculares individuais (Stålberg, 1966) e do jitter neuromuscular (Stålberg et al, 1971;Ekstedt et al, 1974), a EMGFU também permite o estudo da distribuição das fibras musculares nas unidades motoras individuais, denominado densidade de fibras (Gath, Stålberg, 1976).…”
Section: Introductionunclassified